FEIRAS DE MATEMÁTICA NO RIO GRANDE DO SUL: UM PROCESSO FORMATIVO - CLEYTON AVI , PETERSON; PIVA , CLAUDIA; KOLTERMANN BATTISTI , ISABEL; PATRICIA GRAJALES SPILIMBERGO , ANGELA (Salão do Conhecimento, 2020)
Projeto Institucional de Extensão